MRI of Blood–Brain Barrier Permeability in Cerebral Ischemia - Jiang, Quan (2011)
Quantitative measurement of blood–brain barrier (BBB) permeability using MRI and its application to cerebral ischemia are reviewed. Measurement of BBB permeability using MRI has been employed to evaluate ischemic damage during acute and subacute phases of stroke and to predict hemorrhagic transformation. There is also an emerging interest on the development and use of MRI to monitor vascular structural changes and angiogenesis during stroke recovery. In this review, we describe MRI BBB permeability and susceptibility-weighted MRI measurements and its applications to evaluate ischemic damage during the acute and subacute phases of stroke and vascular remodeling during stroke recovery.